Entre grafismos e oralidades: uma interpretação do imaginário da criança ribeirinha Amazônica - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
This study presents an interpretation of the formation of the imaginary child riverside Amazon. The overall objective is geared towards the analysis of the contribution of the symbols present in the Amazonian traditional culture and its implications in the formation of this imaginary child living in coastal communities . Initially , we conjecture that the child internalizes mentally perceived image , and this in turn becomes part of their symbolic universe , so there is no way to think about the construction of the imaginary dissociated from perception , imagination and different forms of languages . We understand that the terms of the symbol and its web of meanings emanating through rivers , forest , animals , customs and cultural traditions Amazon stimulate the imagination of children , especially those who are in close contact with these elements . In this perceptive we concentrate on the following question: How symbols of regional culture contribute to the formation of the imaginary child inserted in river context ? In order to answer this question , we conducted a scientific intervention in riverine settlement Nazareth in Côte Tabocal , located on the left bank of the Amazon River . For this undertaking academic research appropriated different methodological strategies : intervention with 40 children enrolled in the School Hall Our Lady of Nazareth ( research locus ) consisting of interactive dialogue , textual production and use of graphics , expressed in themed designs . The study revealed that direct contact with the images seen daily in the natural habitat , ie , on the banks of rivers , streams , forests and animals , the coming and going in the canoes , fishing and playing stood out as key factors that stimulate the imagination and sharpen increasingly imaginary child who lives in the streams of the Amazon . Finally we conclude that the school amazon river , to make use of the locus where it is located , greatly stimulate the creativity and imagination of the child , because in our opinion the school has a primary role as the perceptions and the transformations of the symbolic universe of the child.
Keywords: Comunidade ribeirinha; Riverside community; Imaginação - Criança; OUTROS